Comparison of the diet composition of red-striped cardinal fish, Apogon margaritophorus, in Talibon, Bohol and concepcion, Iloilo. - Duno, Khrsha M.
This study examined and compared the diet composition of Apogon margaritophorus in Talibon, Bohol and Concepcion, Iloilo. A total of 8 prey items were identified from 301 stomachs examined. Stomach contents were analyzed using numerical analysis where prey items are expressed in terms of frequency of occurrence (FOC). Cluster analysis was used to assess similarities in the composition of prey items in individuals of different size categories, study areas, and years. The results show that similarities are based primarily on sizes, and that differences between areas and years are important considerations. The results show that small sized fish generally feed on small prey types. While larger fish can feed on both small and large prey. Spatial and temporal factors can also affect the diet of A. margaitophorus due to either abundance or unavailability of the prey in a certain site or year.